Survival status and determinants of under-five mortality in Sudan: Evidence from the Multiple Indicator Cluster Survey 2014 - Huda Mohamed Mukhtar AHMED; Hiba Abbas Omer ELKARIB; Mutaz Fikri Mohamed Osman DIGNA (Journal of Health and Social Sciences)
Introduction: Under-five mortality in Sudan declined in the last decade, but the reduction was well below the goal set by the Sudan Health Sector Strategic Plan developed for 2012-2016. This study investigated the risk factors of under-five mortality in Sudan. Methods: Data by the Multiple Indicator Cluster Survey conducted in 2014 by the Central Bureau of Statistics (CBS) and the Federal Ministry of Health, Sudan, were collected. Non-parametric methods such as Kaplan–Meier survival function and log-rank were used to assess the effect of socioeconomic and demo- graphic variables on under-five mortality. Cox hazard proportional and frailty models were carried out to examine predictors of under-five mortality. Results: Our research showed that the risk of death among under-five children vary by states in Sudan. Moreover, Cox proportional and frailty models showed that type of birth (Hazard Ratio (HR) twin birth vs. single birth = 2.7, (95% Confidential Interval [CI] 1.8 to 4.1, P = 0.000), household wealth index (HR rich vs. poor = 0.42, (95% CI 0.20 to 0.87, P = 0.021), previous birth interval less than 2 years (HR Interval < 2 years vs first birth = 2.3, (95% CI 1.6 – 3.4, P = 0.000), and region of residence (HR Northern region vs. Khartoum) = 0.33, (95% CI 0.12 – 0.92, P = 0.035) were statistically significant determinant of under-five mortality in Sudan. Discussion: Based on our findings, all intervention plans targeted to reduce child mortality in Sudan should consider specific determinants of risk. Furthermore, the Cox proportional model jointly with frailty models could be useful for further studies on determinants of under-five mortality.